DETERMINATION OF NATURAL AND ARTIFICIAL RADIONUCLIDES IN SEA WATER AND SEDIMENTS OFF GWADAR COAST, ARABIAN SEA - Akram, M.; Qureshi, R. M.; Ahmad, N.; Solaija, T. J.; Mashiatullah, A.; Ayub, M. A.; Irshad, Saima (The Nucleus, 2020)
Determination of naturally occurring radionuclides (226Ra, 228Ra, 40K) and fission fragment (137Cs) in shallow sea water and sediment samples collected from Gwadar coast, Pakistan has been carried out. The activity detected in various sediment samples ranged from 16.9±2.1 to 31.7±3.2 Bq.kg-1 for 226Ra, 9.8±1.2 to 13.3±1.2 Bq.kg-1 for 228Ra and 152.4±11.4 to 244.4±15.7 Bq.kg-1 for 40K. In water samples the activity detected for 40K ranged from 9.3±0.8 to 17.5±3.0 Bq.l-1. The levels of radioactivity for Gwadar area have been compared with the results published in literature for other regions of the world i.e., Irish sea sediment (226Ra = 23.9 Bq.kg-1, 228Ra = 36.7 Bq.kg-1), Pacific Ocean sediments, (226Ra = 21.41.1 Bq.kg-1), Indian Ocean sediment, (226Ra = 13.8 Bq.kg-1, 228Ra= 26.7 Bq.kg-1, 40K = 297.0 Bq.kg-1) and Bay of Bangal (226Ra = 13.9 to 25.2 Bq.kg-1, 40K = 118.3 to 651.9 Bq.kg-1). The level of 40K for Irish sea water is 11.4 Bq.l-1. The mean values of radium equivalent activity, absorbed dose rate and effective dose are 58 Bq.kg-1, 27 nGy.h-1 and 0.03 mSv.y-1 respectively. The value of effective dose is much below the level of 1.0 mSv.y-1, for general public based on stochastic effects recommended by International Commission on Radiological Protection (ICRP). As previously no data on radioactivity of coastal environment of Pakistan is available, the data presented here will serve as baseline for radionuclide concentration in seawater and sea sediments of the study area, and will be included in International Atomic Energy Agency, IAEA’s, Asia Pacific Marine Radioactivity Database (ASPAMARD).